Implementation of a Security System in IaaS Cloud Server through an Encrypted Blockchain - Vivekanandam, B.; Midhunchakkaravarthy (Journal of Soft Computing Paradigm, 2022)
Infrastructure as a Service (IaaS) is a kind of cloud sharing service allocated to different category of application at the same time. The shared cloud services are provided through internet for computing, networking, and data storage applications. The utilization of IaaS reduces the maintenance and installation cost of physical hardware modules at the base station. The cloud service providers configure their available cloud components with respect to the suitability of the user requirements. The security protocol available in the IaaS servers are usually better than the traditional local servers. However, the IaaS servers are also open to attacks when the modules encounter misconfiguration and vulnerabilities. The work enforces an encrypted blockchain model for enhancing the quality of service in the IaaS systems on handling image data.